Peran K.H. Saifuddin Zuhri Sebagai Menteri Agama Pada Masa Orde Lama (1962 – 1967) - Elya Faridah; Ajid Hakim (UIN Sunan Gunung Djati Bandung, 2020)
This study deals with the role of KH. Saifuddin Zuhri as Minister of Religion using biographical approach by describing his passion in improving the quality of Islamic education, particularly the Islamic university. He plays a vital role in the development of Islamic universities, namely the State Islamic Institute (IAIN). IAIN is a center for high-level teaching and education activities for Muslim youth. During a period of leadership of KH Saifuddin Zuhri at the Ministry of Religious affair, he succeeded in inaugurating the IAIN at the provincial level by naming the universities according to figures from the region and 14 IAIN branches at the district level. / city. To support the improvement of the quality of teaching staff and infrastructure for higher education, K.H. Saifuddin Zuhri seeks to make a policy, namely by sending students to study abroad on scholarships, establishing a translation and publishing agency for the Qur'an, managing the distribution of religious books to schools and Islamic boarding schools. In addition, he also made policies to appoint honorary religious teachers and the equivalent of madrasa diplomas. For his efforts, IAIN Sunan Kalijaga Yogyakarta gave a sign of honor for a professor in the field of da'wah with the title